2015
DOI: 10.5267/j.ijiec.2014.9.003
|View full text |Cite
|
Sign up to set email alerts
|

Ann modeling of kerf transfer in Co2 laser cutting and optimization of cutting parameters using monte carlo method

Abstract: In this paper, an attempt has been made to develop a mathematical model in order to study the relationship between laser cutting parameters such as laser power, cutting speed, assist gas pressure and focus position, and kerf taper angle obtained in CO 2 laser cutting of AISI 304 stainless steel. To this aim, a single hidden layer artificial neural network (ANN) trained with gradient descent with momentum algorithm was used. To obtain an experimental database for the ANN training, laser cutting experiment was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Finally, for the constant laser power of 3.6 kW (Figure 2c), an increase in assist gas pressure as well as cutting speed results in a negligible increase of kerf taper angle values. This is in accordance with the results reported by Madić et al [34]. In that research, it has been reported that for certain levels of laser power the effects of assist gas pressure and cutting speed on the change in kerf taper angle may be negligible.…”
Section: Resultssupporting
confidence: 93%
“…Finally, for the constant laser power of 3.6 kW (Figure 2c), an increase in assist gas pressure as well as cutting speed results in a negligible increase of kerf taper angle values. This is in accordance with the results reported by Madić et al [34]. In that research, it has been reported that for certain levels of laser power the effects of assist gas pressure and cutting speed on the change in kerf taper angle may be negligible.…”
Section: Resultssupporting
confidence: 93%
“…Due to the ability to find a set of trade-off solutions in a single simulation run, inclination toward the adaptation of AI-based optimization methods especially evolutionary multi-objective optimization (EMO) algorithm shows a growing interest not only to control and predict the behavior of the phenomenon, but also to accomplish a common goal of improving machining performance. Various researchers have employed methods which include statistical and analytical approaches for mathematical modeling (Ciurana et al 2009;Kibria et al 2013;Mishra and Yadava 2013;Madić et al 2015) in order to predict the responses and for multi-response optimization (Dhupal et al 2008;Wang et al 2016;Giorleo et al 2016) in order to control the process parameters during laser micromachining process. Recently, Shivakoti et al (2017) highlighted the use of fuzzy TOPSIS method for the selection of optimal laser micromarking process parameters to improve the marking performance on high strength temperature resistance material such as gallium nitride (GaN).…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies [7][8][9][10][11][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] do not consider the spatial characteristics of laser beams. Nevertheless, these are accounted for by the FPP, which is one of the key factors of the cutting process.…”
Section: Laser Beam Shape Position and Distortionmentioning
confidence: 99%
“…The details of this approach are described by Orishich et al 12 Only in one study was the FPP used as the input optimization parameter. 28 It is obvious that the beam waist should always be located on the thin-section workpiece's surface (FPP ¼ 0) during cold ablation cutting at extremely high intensities produced by sharp beam focusing. 33 In gas-assisted laser cutting of medium-and thick-section metals, the beam waist rarely coincides with any of the material surfaces of the cutting sheet or melt pool.…”
Section: Laser Beam Shape Position and Distortionmentioning
confidence: 99%
See 1 more Smart Citation